Turning to the dark side: Challenging the hegemonic positivity of the creativity discourse - Josefsson Iva; Blomberg Annika (Elsevier, 2022)
Using a Laclauian discourse approach this paper challenges the hegemony of articulations framing creativity as
good, necessary, and as a source of valuable outcomes for organizations and individuals. Instead, this paper
argues that creativity has a ‘dark side’, referring to that which is harmful and may result in pain, loss or suffering.
We analyze and expose the hegemonic positivity of the creativity discourse within organization studies and
discuss the implications of this hegemony. We conclude that the dark side of creativity has been subverted in the
discourse and requires further scholarly exploration. To promote a greyer research agenda of creativity in organizations, we offer three theorizations of the dark side of creativity as antagonisms to the hegemony – the
individual, collective, and critical. By challenging the hegemonic positivity of creativity and by providing a
number of research imaginaries, this paper invites scholars to broaden the discourse and to embrace a more
greyer understanding of creativity in organization studies.